PENGARUH LAMA FERMENTASI TERHADAP RANCIDITAS MINYAK KELAPA YANG DIPRODUKSI SECARA TRADISIONAL - Paulus Valentino Patty (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: People of Maluku has the habit to cultivate oil palm fruit into oil by fermentation. The fermentation process that traditionally takes place at varying fermentation makes it easier rancid oil. This study aims to determine whether there was an effect on the fermentation time ranciditas coconut oil traditionally produced, ranciditas measured using a peroxide. Methods: The study was conducted at the Laboratory of Basic Chemistry Pattimura University in Ambon on 10 September 2014 with a long fermentation 0 hours (control), 6 hours, 12 hours, 18 hours, 24 hours, and analyzed using descriptive analysis. Results: There is a very real effect ranciditas level lower palm oil contained in the fermentation 6 hours with an average rate of 0.0988 peroxide. Conclusion: Long fermentation influence on ranciditas coconut oil traditionally produced. The impact that an increase in peroxide value is the average with increasing length of fermentation.